Edmund de Waal - Giorgio Morandi - De Waal, Edmund 1964-; Nilsson, Bo 1954-; Veiteberg, Jorunn 1955-; Sjöberg, Fredrik 1958- (Artipelag, 2017)
The exhibition at Artipelag highlights about fifty works from Morandi's career. The very earliest works are from 1921 and the latest from 1963. A significant portion of the Morandi paintings featured in the exhibition are still life of ceramic household items and there are also a handful of landscape paintings included. The paintings are complemented by drawings, etchings and watercolours, which illustrate Morandi's artistic range.0De Waal's characteristic series of porcelain pots shifts the attention from each pot to their grouping as a whole, the created spaces between them and how the viewer's gaze flows through the art work. Artipelag's exhibition will be the first time that de Waal's works are presented in Sweden and will include close to forty art works from 2012 to 2017. About ten of these works are new, stemming from a dialogue with the works of Morandi; de Waal has on numerous occasions emphasized Morandi as one of his greatest sources of inspiration. Exhibition: Artipelag, Gustavsberg, Sweden (07.04. -1.10.2017)
Exhibition: Morandi/Edmund de Waal, 07 April-01 October 2017 Artipelag
Titelblatt auf Seite 17
Keywords: De Waal, Edmund -- 1964-; Morandi, Giorgio -- 1890-1964; Geschichte 1921-1963; Porzellan; Malerei; Ausstellungskatalog -- Artipelag -- 07.04.2017-01.10.2017 -- Gustavsberg